THE BODY AND THE LIMITS OF CORPOREALITY IN "THE CRYSTAL FRONTIER" BY CARLOS FUENTES (Journal of Contemporary Philology, 2018)
The Crystal Frontier, аpolyphonic novelby Carlos Fuentes, deals with a number of themes such as migration, class differences, xenophobia, corruption and deconstructs a lot of linguistic, social, cultural, symbolic boundaries, re-examining furthermore the boundaries  between  genres. In  this  paper,  we  further analyze  the  work  from  the perspective of the corporeality and the body that represents a starting point from which many  borders  are  delineated:  those  imposed  by  fashion,  gender,  sexual  orientation, those derived from the power relations or theapparent freedom of the  female body, those who stand between us and our past, between life and death.
Keywords: body; liminality; The Crystal Frontier; Carlos Fuentes